Understanding turnover intention in Gen Z: Servant leadership and ethical climate in organization - Putri, Safira Dwi Tyas; Salendu, Alice; Pahlawan, Aditya Wira (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
This study investigates the relationship between servant leadership and turnover intention among Generation Z employees in Indonesia, focusing on the mediating role of principled ethical climate and the moderating role of interpersonal justice. A cross-sectional quantitative approach was employed, collecting data from 317 Gen Z employees with at least one year of direct supervision. Data were analyzed using the Hayes PROCESS Model. The findings reveal that servant leadership directly negatively affects turnover intention, emphasizing its effectiveness in reducing employees’ desire to leave the organization. However, servant leadership also positively influences a principled ethical climate, significantly increasing turnover intention. This highlights a dual effect: while servant leadership can enhance retention, it also fosters a principled ethical environment that may be perceived as restrictive by Gen Z employees, who prioritize flexibility, leading to higher turnover intention. Interpersonal justice significantly moderates the relationship between servant leadership and a principled ethical climate. High levels of interpersonal justice weaken the positive influence of servant leadership on a principled ethical environment. Nevertheless, the indirect effect of interpersonal justice on turnover intention is insignificant, indicating that its role primarily impacts organizational climate rather than directly influencing turnover intention. This study contributes to the literature by elucidating the complex interplay between servant leadership, ethical climate, and justice in the Gen Z workforce. Practically, organizations are encouraged to adopt servant leadership styles while promoting a flexible and equitable culture to retain Gen Z talent. Future research could use longitudinal or cross-cultural approaches to explore these dynamics further.